2017
DOI: 10.18632/oncotarget.14773
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1: a potential chemokine widely involved in the process spinal metastases

Abstract: ObjectivesThe aim of our study was to investigate the general mechanism of spinal metastases from five different primary cancers: lung cancer, breast cancer, liver cancer, prostate cancer, and kidney cancer.ResultsFrom microarray analysis and validation by real-time polymerase chain reaction, CX3C chemokine ligand 1 (CX3CL1) appeared to be a potential chemokine widely involved in the process of spinal metastases. Further studies revealed that, compared with normal controls, serum samples from patients with spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…However, recent research has demonstrated that the CX3CL1/CX3CR1 axis is involved in the survival, adhesion, and migration of malignant tumor cells, including breast cancer 13 , 14 . In our previous research, we first demonstrated that CX3CL1 was associated with the process of spinal metastases from different malignant primary tumors, including breast cancer 15 . Unfortunately, the molecular mechanism of breast cancer metastasizing to the spine still remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has demonstrated that the CX3CL1/CX3CR1 axis is involved in the survival, adhesion, and migration of malignant tumor cells, including breast cancer 13 , 14 . In our previous research, we first demonstrated that CX3CL1 was associated with the process of spinal metastases from different malignant primary tumors, including breast cancer 15 . Unfortunately, the molecular mechanism of breast cancer metastasizing to the spine still remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…CX3CL1 is involved in the invasion and metastasis of various malignant tumor types and promotes tumor metastasis via chemotaxis and adhesion of circulating tumor cells (Tardáguila et al, 2013;Liu et al, 2016). Our previous study found that CX3CL1 was highly expressed in spinal osseous tissues compared with limb osseous tissues, and the patients with spinal metastases exhibited high levels of CX3CL1 (Liu et al, 2017). The above results suggested that CX3CL1 serves essential roles in tumor cell metastasis to the spine.…”
Section: Discussionmentioning
confidence: 82%
“…Vertebral cancellous bones, as a preferential district for bone metastases, are highly efficient at arresting circulating cancer cells from low-velocity bloodstream. Furthermore, CX3CL1, which is rich in vertebral microenvironments (Liu et al, 2017), chemo-attracts many tumor cells from blood circulation to the spine. CX3CL1 functions as an adhesion molecule for arresting circulating tumor cells in spine microvasculature (Ostuni et al, 2014;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Inverse associations between the level of circulating CX3CL1 and risk of cancer on other sites have also been reported . At the same time, observations point to possible involvement of CX3CL1 in the development of spinal metastases in several cancers, including prostate cancer . Our observations may reflect a possible role of CX3CL1 in antitumor immunity against prostate cancer.…”
Section: Discussionmentioning
confidence: 99%